1995
DOI: 10.1007/bf01187669
|View full text |Cite
|
Sign up to set email alerts
|

Cortical processing of vowels and tones as measured by event-related desynchronization

Abstract: Event-Related Desynchronization (ERD) and Synchronization (ERS) were studied in 20 normal subjects during a Sternberg-type auditory memory-scanning paradigm. Half of the subjects performed the experiment with vowels and the other half with tones as stimuli. The stimuli consisted of 100 msec long synthesized vowels and 100 msec long tones produced by eight different synthesized instruments. In this paradigm each trial started with the presentation of a visual warning signal, after which a four-stimulus set was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…3) both in the upper (8 Hz) and lower (12 Hz) bands, increased after 200 ms and reached its maximum at around 500 ms. In the literature, a similar time course of induced alpha ERD in response to auditory stimuli has been reported in adults when subjects were required to compare a probe stimulus to a set of previously heard stimuli (Karrasch et al, 1998;Krause et al, 1995Krause et al, , 2001 and when subjects had to detect a target stimulus in an oddball paradigm (Mazaheri and Picton, 2005). These experiments commonly showed that alpha ERD began approximately 300-600 ms after stimulus onset, followed by a peak of ERD around 600-800 ms, and ended around 1500-2000 ms.…”
Section: Non-phased-locked Alpha Erd and Stimulus Processingmentioning
confidence: 70%
See 2 more Smart Citations
“…3) both in the upper (8 Hz) and lower (12 Hz) bands, increased after 200 ms and reached its maximum at around 500 ms. In the literature, a similar time course of induced alpha ERD in response to auditory stimuli has been reported in adults when subjects were required to compare a probe stimulus to a set of previously heard stimuli (Karrasch et al, 1998;Krause et al, 1995Krause et al, , 2001 and when subjects had to detect a target stimulus in an oddball paradigm (Mazaheri and Picton, 2005). These experiments commonly showed that alpha ERD began approximately 300-600 ms after stimulus onset, followed by a peak of ERD around 600-800 ms, and ended around 1500-2000 ms.…”
Section: Non-phased-locked Alpha Erd and Stimulus Processingmentioning
confidence: 70%
“…Since we used a passive listening task, the difference between violin and noise sounds cannot be associated with cognitive demands directly. However, it is reasonable to assume that the violin sound is more meaningful compared to white noise, and thereby initiates more complex auditory processing which leads to the pronounced upper alpha ERD as shown in adults (Krause et al, 1995). Thus, we propose that the upper alpha ERD induced by an auditory stimulus can index processes of stimulus feature analysis and registration, as well as subsequent cognitive processes in both children and adults.…”
Section: Distinction Between Upper and Lower Alpha Erdmentioning
confidence: 94%
See 1 more Smart Citation
“…However, task-dependent synchronization of alpha oscillations in association with the regulation of motor behaviour, attention, memory, and lexical processes (e.g. Pfurtscheller et al, 1997;Krause et al, 1995;Hari and Salmelin, 1997;Karrasch et al, 1998) has since been proposed to reflect specific operations of higher brain functioning rather than cortical idling (Kolev et al, 1999.…”
Section: Alpha Rhythmsmentioning
confidence: 99%
“…It is now acknowledged that human scalp recorded EEG oscillatory responses at different frequencies can be associated with several distinct aspects of cognitive functioning ranging from stimulus processing, attention, working memory, encoding and recognition to long-term memory [Krause et al, 1995[Krause et al, , 1996Basar et al, 1999Basar et al, , 2001aKlimesch, 1999;Ward, 2003]. For example, responses in the theta frequency band (typically defined as $4-7 Hz) have been related to encoding and recognition of information [for a review see Klimesch, 1999], memory-load demands [Krause et al, 2000c] and lexico-semantic processing [Bastiaansen et al, 2005].…”
Section: Introductionmentioning
confidence: 99%